Inhibition of the Nuclear Receptor RORγ and Interleukin-17A Suppresses Neovascular Retinopathy: Involvement of Immunocompetent Microglia. Issue 6 (June 2016) - Talia, Dean M.; Deliyanti, Devy; Agrotis, Alex; Wilkinson-Berka, Jennifer L.
Abstract : Objective—: Although inhibitors of vascular endothelial growth factor (VEGF) provide benefit for the management of neovascular retinopathies, their use is limited to end-stage disease and some eyes are resistant. We hypothesized that retinoic acid–related orphan nuclear receptor γ (RORγ) and its downstream effector, interleukin (IL)-17A, upregulate VEGF and hence are important treatment targets for neovascular retinopathies. Approach and Results—: Utilizing a model of oxygen-induced retinopathy, confocal microscopy and flow cytometry, we identified that retinal immunocompetent cells, microglia, express IL-17A. This was confirmed in primary cultures of rat retinal microglia, where hypoxia increased IL-17A protein as well as IL-17A, RORγ, and tumor necrosis factor-α mRNA, which were reduced by the RORγ inhibitor, digoxin, and the RORα/RORγ inverse agonist, SR1001. By contrast, retinal macroglial Müller cells and ganglion cells, key sources of VEGF in oxygen-induced retinopathy, did not produce IL-17A when exposed to hypoxia and IL-1β. However, they expressed IL-17 receptors, and in response to IL-17A, secreted VEGF. This suggested that RORγ and IL-17A inhibition might attenuate neovascular retinopathy. Indeed, digoxin and SR1001 reduced retinal vaso-obliteration, neovascularization, and vascular leakage as well as VEGF and VEGF-related placental growth factor. Digoxin and SR1001 reduced microglial-derived IL-17A and Müller cell and ganglion cell damage. The importance of IL-17A in oxygen-induced retinopathy was confirmed by IL-17A neutralization reducing vasculopathy, VEGF, placental growth factor, tumor necrosis factor-α, microglial density and Müller cell, and ganglion cell injury. Conclusions—: Our findings indicate that an RORγ/IL-17A axis influences VEGF production and neovascular retinopathy by mechanisms involving neuroglia. Inhibition of RORγ and IL-17A may have potential for the improved treatment of neovascular retinopathies. Abstract : Supplemental Digital Content is available in the text.